(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The potential of Wild Guinea fowl for domestication is still not totally exploited as there are needs for improved variability. This study was done in order to analyze egg features of wild Guinea fowl, Numida meleagris. A total of 27 eggs were obtained from three different markets in Ogun state and they were assessed for both external and internal features. Highest values of Haugh unit, albumen width, albumen height and egg shape index of 89.28%, 41.36mm, 6.34mm and 81.56% were recorded in eggs collected at Sabo market respectively. Highest egg width-37.57mm, egg weight- 34.38g and yolk diameter- 34.94mm were reported from eggs sourced from Itoku market while highest egg length-46.99mm, yolk height-16.29mm, yolk index-48.24% and albumen index- 24% were recorded in eggs obtained at Oke-Aje markets. Eggs internal and external parameters were not significantly different between the three markets (p > 0.05) but correlation between the parameters varied from positive to negative. Considerable association were found between egg shape index and egg’s weight, albumen index and albumen width, weight of eggs and egg length, using Pearson’s correlation coefficients with p-value of significance at 0.05 and 0.01. It is concluded that the wild eggs of guinea fowls sourced from the three markets had good quality traits in terms of the Haugh unit.